Corneal thickness and endothelial cell density in children with type 1 diabetes mellitus - Sheldon Ignatius Fernandes; Shubha Nagpal (Oman Journal of Ophthalmology, 2019)
BACKGROUND: The aim of this study was to detect the effect of diabetes on the corneal endothelium in patients of Type 1 diabetes in the pediatric age group and to compare them with age-matched controls. Further, it was proposed to establish any correlation between these changes and risk factors of diabetes, viz., age, duration of diabetes, and hemoglobin A1c (HbA1c) values. MATERIALS AND METHODS: This was a prospective cross-sectional study. Fifty children with Type 1 diabetes, between the ages of 7 and 17 years (average, 12.16 ± 2.63 years), and fifty healthy age-matched controls (average 12.28- ±3.00 years) were examined. The central corneal thickness (CCT) and endothelial cell density (CD) were assessed by the Topcon SP-1P specular microscope. The duration of diabetes (average, 3.91 ± 1.65 years) and the HbA1c values (average, 10.92 ± 2.28) were also noted. RESULTS: The average CCT in the diabetics was 525.16 ± 33.14 μ and in the controls 513.44 ± 29.46 μ. This was significantly higher (P = 0.015). The average endothelial CD in the diabetics was 3039.64 ± 292.84 cells/mm2 and in the nondiabetics 3360.41 ± 268.04 cells/mm2. This was significantly lower (P < 0.001). A significant correlation was found between the endothelial CD and age of the diabetic patients (P = 0.008). However, there was no significant correlation between the endothelial CD and the CCT with either duration of diabetes or HbA1c. CONCLUSIONS: A significant decrease in the endothelial CD and increase in the CCT occurs in children and adolescents with Type 1 diabetes. With the age of the diabetic patients, the endothelial CD significantly reduces. However, duration of diabetes and HbA1c do not affect these values.